2020
DOI: 10.1002/ett.3903
|View full text |Cite
|
Sign up to set email alerts
|

Structured analysis/synthesis compressive sensing‐based channel estimation in wideband mmWave large‐scale multiple input multiple output systems

Abstract: The hybrid architecture still be the most attractive solution for the analog‐digital beamforming in millimeter wave (mmWave) large‐scale multiple input multiple output (LS‐MIMO) systems, since it provides the best trade‐off between the achievable rate and the power consumption. When maximizing performance metrics, channel knowledge is required to optimally design the hybrid beamforming. The channel estimation (CE) is essential for wideband mmWave LS‐MIMO to substantially enhance data rates, however, is a chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…This indicated that the independent treatment of each stage did not allow the joint utilization of the channel sparsity and low-rank properties [27].The practical implementation of large antenna arrays, hybrid precoding, and the sparsity of mm-Wave channel prevented traditional CE methods designed for a lower-frequency MIMO system applicable for the mm-Wave -Ma-MIMO system [28]. Hence, specific CE techniques for mm-Wave-Ma-MIMO systems were proposed in [29][30][31][32][33].In [28], [30,31], the Eigen-decomposition based algorithms using the availability of low rank channel covariance matrices were designed for CE.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…This indicated that the independent treatment of each stage did not allow the joint utilization of the channel sparsity and low-rank properties [27].The practical implementation of large antenna arrays, hybrid precoding, and the sparsity of mm-Wave channel prevented traditional CE methods designed for a lower-frequency MIMO system applicable for the mm-Wave -Ma-MIMO system [28]. Hence, specific CE techniques for mm-Wave-Ma-MIMO systems were proposed in [29][30][31][32][33].In [28], [30,31], the Eigen-decomposition based algorithms using the availability of low rank channel covariance matrices were designed for CE.…”
Section: Related Workmentioning
confidence: 99%
“…Unfortunately, the complex nature of these CE algorithms was high to a large extent and required large overhead to obtain reliable channel covariance matrices. To eliminate this problem, [32,33] proposed the CS based CE methods by exploiting the sparsity of mm-Wave channel in the angular domain and incorporating the hybrid architecture, while dealing with the management of multi-cell inter-cell and multi-user intra-cell interference in ultra-dense heterogeneous networks as well as beam squint effect. But, the complexity was still of high level due to the nonlinear optimization; their effectiveness highly depended on the Restricted Isometry Property (RIP) as well as estimation of the whole cosparse mm-Wave channel instead of its gain only.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…However, massive MIMO systems cannot be directly adopted in mmWave frequency band, because each antenna needs to be connected to a radio frequency (RF) chain, which results in high hardware cost and power consumption of massive MIMO systems 19,20 . In order to solve this problem, one feasible solution is to employ the discrete lens antenna (DLA) array 21 .…”
Section: Introductionmentioning
confidence: 99%